Searching for new annual legumes suitable for pasture establishment in Southern Europe - Re G.A.; Dettori D.; Franca A.; Porqueddu C.; Sulas L. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
The high plant biodiversity of Mediterranean basin, shaped from both the millennial agro-pastoral activity and the pedo-climatic variability, has produced a natural selection of pasture species, suitable for several uses in farming systems. Many of the recently released Australian annual legumes varieties are not always suitable for pasture establishment in southern Europe, mainly because of their early flowering and high hardseededness, which affect the persistence capability. In order to clarify the low persistence of the Australian varieties and to identify new interesting materials for the Mediterranean forage scene, ten accessions of Lotus ornithopodioides, Ornithopus compressus, O. sativus, Trifolium hirtum, T. mutabilis and T. spumosum were compared in North-Sardinia. These accessions, were evaluated for bio-agronomic traits as vigour, phenology, seed production and hardseedness breakdown. Results revealed the potential suitability of many of tested materials for both Mediterranean pasture improvement purposes and multifunctional uses.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)